Research on dynamic characteristics of large deformation shearer cable based on absolute node coordinate formulation method. - Lijuan Zhao; Haining Zhang; Feng Gao; Liguo Han; Man Ge (PLoS ONE, 2023)
The development of intelligent and unmanned coal mining has put forward higher requirements on the service life and dynamic reliability of shearer cables. However, it is difficult to comprehensively consider the complexity of hosting conditions of coal mining working face and the dynamic characteristics of cables in different towing systems in the design and development of cables. The cables are periodized by pitch and have the same cross-sectional structure and properties. Based on the homogenization theory and volume average principle, the cable was assumed to be an orthotropic elastomer, and the tensile experimental method and finite element method were combined to calibrate the cable equivalent mechanical parameters. Based on the Absolute Node Coordinate Formulation (ANCF) method, the rigid-flexible coupled virtual prototype co-simulation model of shearer cable towing system was constructed to obtain the kinetic and kinematic parameters of each node of the cable and study the dynamic gradual change characteristics of the cable in different working areas. This research method has an important theoretical significance and engineering application value for the acquisition of dynamic characteristic parameters of shearer cables and the optimal design and dynamic reliability of cables.